2007
DOI: 10.1038/ni1538
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of transcription factor IRF1 to the interferon-γ–interleukin 12 signaling axis and TH1 versus TH-17 differentiation of CD4+ T cells

Abstract: Interleukin-12 (IL-12) and interferon-gamma (IFN-gamma) drive T helper type 1 (T(H)1) differentiation, but the mechanisms underlying the regulation of the complicated gene networks involved in this differentiation are not fully understood. Here we show that the IFN-gamma-induced transcription factor IRF1 was essential in T(H)1 differentiation by acting on Il12rb1, the gene encoding the IL-12 receptor beta1 subunit (IL-12Rbeta1). IRF1 directly interacted with and activated the Il12rb1 promoter in CD4+ T cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 49 publications
6
101
0
1
Order By: Relevance
“…For instance, OX40 engagement inhibits IL-10 production along Th2 differentiation [42] and during anti-viral immune responses [43]. Moreover, we show here that OX40 signal may regulate IL-10 secretion through the modulation of IRF1, a Th1-related transcription factor [44]. We found IRF1 expressed in tumor-infiltrating but not peripheral Treg cells producing or not IL-10, respectively.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…For instance, OX40 engagement inhibits IL-10 production along Th2 differentiation [42] and during anti-viral immune responses [43]. Moreover, we show here that OX40 signal may regulate IL-10 secretion through the modulation of IRF1, a Th1-related transcription factor [44]. We found IRF1 expressed in tumor-infiltrating but not peripheral Treg cells producing or not IL-10, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…However, we could not detect any Foxp3 downregulation in tumor-infiltrating compared with peripheral Treg cells, or in IL-10-producing versus IL-10-negative Treg cells. IRF1 is a transcription factor playing essential roles in Th1 differentiation, inducing IL-12Rb1 in CD4 1 T cells [44]. Germane is the expression of IL-12Rb1 in lamina propria Treg cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…The signalling pathways that promote innate cytokines that drive induction or expansion of Th17 cell have also received some attention [72]. Although a great deal is known about TLR-induced signalling in macrophages or DC that mediate IL-1, TNF-a and IL-12 production, less is known about the pathways that promote IL-23 production, except that they appear to be distinct from those that mediated IL-12-driven Th1 responses [73]. We have preliminary evidence that distinct signalling pathways are involved in TLR/NLR agonist-induced IL-23 and IL-12p70 production by murine DC (Brereton and Mills, unpublished data).…”
Section: T-cell Subtypes That Secrete Il-17mentioning
confidence: 99%
“…We have preliminary evidence that distinct signalling pathways are involved in TLR/NLR agonist-induced IL-23 and IL-12p70 production by murine DC (Brereton and Mills, unpublished data). It has been reported that MyD88-mediated activation of NF-kB, IRF-1, IRF-5 and IRF-8 plays important roles in the expression of IL-12p35 and IL-12p40 genes and in driving Th1 in responses, whereas NF-kB, IRF3, IRF5 may be involved in IL-23 and IL-17 production [72,73]. In addition, it has been demonstrated that signalling through the C-type lectin dectin-1 in DC for IL-6, TNF-a and IL-23 production and consequent Th17 development involves Syk and CARD9 [65].…”
Section: Intracellular Signalling Molecules and Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation